Peran Kepala Madrasah Sebagai Motivator dan Inovator Peningkatan Mutu Lembaga - Munardji Munardji (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Improving the quality of education is closely related to improving human resource. Meanwhile, the quality of human resources at school is a partly relied to the quality of the principal. A principal is responsible to the success or failure of education. The problem lies upon the difficulty to find a credible principal who can manage the institution quite well. The jobs of a principal are (1) encourage the teachers to have continuous professional development, (2) become role model for everybody at school, (3) make innovation for the institution.